Effect of Adding Hydrochloric Acid to Alumina Oxide (LAO) Clay on Adsorption Capacity of Pb and Cd Metal Ions - C.M. Bijang; T. Azis; T. Timisela; Nohong; A. T. Nurwahida (International Journal of Acta Material, 2024)
Research has been conducted on the application of Ouw Natural Clay (LAO) as an adsorbent for Pb metal ions and Cd metal ions, following the addition of hydrochloric acid (HCl). The concentrations of HCl used were 2, 3, and 4 M. Characterization was performed to evaluate the differences in clay characteristics before and after the addition of HCl. The Surface Area Analyzer (SAA) was utilized for characterization, specifically to determine the specific surface area, pore volume, and pore size. The results of the characterization indicated an increase in specific surface area, from 31.37 m2/g for pure LAO to 99.68 m2/g for LAO-HCl 4 M. Furthermore, the addition of hydrochloric acid to the Ouw clay natural resulted in a reduction in the capacity to adsorb Pb metal ions and Cd metal ions.